Discorsi di Taverna: Ovvero discorsi postumi sulla genesi e lo sviluppo di 1,2,3 crisi ovvero la crisi salvata dai ragazzi(ni) - Cappadona, Gabriele; Provinzano, Giuseppe (Mimesis Journal, 2016)
Discorsi di Taverna is a dialogue and the presentation of a dramaturgical process made by the artistic collective Babel Crew. Giuseppe Provinzano, author and actor, together with Gabriele Cappadona, economist and dramaturg of the play 1,2,3 crisi ovvero la crisi salvata dai ragazzi(ni), have written a dialogue that they themselves have had in the Tavern that gives the title to their contribution to the revue. The dialogue is to be read aloud. The play is singular, is focused on the economic crisis explained to young people, it has 28 possible story lines and 12 different endings. The final is decided by audience.